Cultura de la contribución en los ciudadanos de Duitama. (2021)
The objective of this research is to analyze the role played by the contribution culture in the inhabitants of the city Duitama. For this purpose, the definition of Law 223 of 1995 is taken as a basis, by which rules on tax rationalization are issued and other provisions are dictated. The DIAN is assigned a very important task for the sensitization and training of citizens, as a fundamental actor in the sustainability and growth of the Nation based on their contribution. (National Tax and Customs Directorate- DIAN-21 July 2021). The qualitative method was used, through the development of three types of instruments which are composed of a questionnaire applied to the inhabitants of the city, interviews with teachers and a group, which allows to know in depth what knowledge the inhabitants of the city of Duitama have regarding taxes and the role played by the culture of contribution. With the result of the surveys, it can be deduced that it is of vital importance that people know what taxes exist, who creates them, what is the justification or financial purpose that makes evident the evident From this, it seeks that each citizen understands the role they have in contributing to the construction of a fair and equitable country, and that behaviors are evaluated according to the goals achieved with the tax cycle.